Grazing Effects on Mongolian Steppe Vegetation—A Systematic Review of Local Literature - Munkhzul, Oyunbileg; Oyundelger, Khurelpurev; Narantuya, Naidan; Tuvshintogtokh, Indree; Oyuntsetseg, Batlai; Wesche, Karsten; Jäschke, Yun (Frontiers in Ecology and Evolution, 2021)
The Mongolian steppes with a long history of nomadic pastoralism cover a large area of the Palaearctic steppe biome and are still relatively intact. As livestock number has increased over the last two decades, grazing has been considered as the main reason of pasture degradation. However, the impact of grazing on vegetation dynamics, and its interaction with climate, is still not clear. We reviewed 44 publications in Mongolian language, covering 109 sites in five main steppe types, i.e., desert, dry, meadow, mountain, and high mountain steppe, with a mean annual precipitation and temperature range from 120 to 370 mm and from −6 to +5°C, respectively. We calculated relative changes in vegetation cover, species richness, and aboveground biomass from heavily grazed with respect to lightly/non-grazed conditions. Multiple linear regression models were used to test the impact of environmental factors, i.e., mean annual precipitation, coefficient of variation for precipitation, mean annual temperature and elevation. Grazing had a stronger effect on the vegetation of dry, desert and high mountain steppes, whereas its effect was less pronounced in the meadow and mountain steppes with mesic climate and high productivity. Vegetation cover, species richness and aboveground biomass were reduced by heavy grazing in the dry, desert and high mountain steppes. In the meadow steppes, grazing reduced vegetation cover, but increased richness and had nearly no effect on biomass. In the mountain steppe, richness and cover were not affected, but biomass was reduced by heavy grazing. Additionally, grazing effects on biomass tended to be more pronounced at sites with higher amounts of annual precipitation, and effects on cover changed from negative to positive as elevation increased. In conclusion, grazing effects in Mongolian steppes are overall negative in desert, dry and high mountain steppes, but no or even positive effects are found in meadow and mountain steppes. Especially, heavy grazing showed a detrimental effect on all vegetation variables in desert steppes, indicating the existence of combined pressure of climate and grazing in arid habitats, making them potentially sensitive to overgrazing and climate change. Grassland conservation and management should consider characteristics of different steppe types and give importance to local environmental conditions.